Mechanisms of change within motivational interviewing in relation to health behaviors outcomes: A systematic review. Issue 4 (April 2015) - Copeland, Lauren; McNamara, Rachel; Kelson, Mark; Simpson, Sharon
Highlights Systematic review: mechanisms of motivational interviewing and health behavior not addictions. Motivation and MI spirit appear to be the most promising mechanisms of MI. A potential causal chain, including therapist behavior and change talk was found. Mechanisms should be tested via mediation analysis to test the predictive validity.